Periostin and IFN-γ levels in serum and nasopharyngeal aspirate in infants with viral-induced wheezing - 2 year follow-up - Mileva, Sirma; Ivanova-Todorova, Ekaterina; Tumagelova-Yuzeir, Kalina; Ivelina, Trifonova T; Korsun, Neli S; Alexiev, Venelin A (The Turkish Journal of Pediatrics, 2022)
Background. The present study assesses the immune response in children with viral-induced wheezing by examining the two factors-interferon-gamma (IFN-γ) and periostin in serum and nasopharyngeal aspirate (NPA). The aim was to find a pattern with the severity and frequency of wheezing episodes. Methods. Sixty-nine infants (40 boys and 29 girls), with a mean age of 11.4±6 (2 - 23) months, hospitalized with a first or recurrent episode of bronchial obstruction were enrolled in this study. The serum and NPA concentrations of IFN-γ and periostin were assessed by ELISA methodology. Fifty of the children (72%) were followed for 2 years. Results. We detected lower NPA IFN-γ production in boys, infants with atopic status, family history of asthma, and respiratory syncytial virus infection. Recurrent wheezing in children was associated with a twice lower concentration of IFN-γ in NPA compared to those with the first episode (7.1 vs. 14.8 pg/ml, p=0.05). Higher serum periostin level was established in children over 12 mo in the group of recurrent wheezers with persistent manifestations compared to those without symptoms during the follow-up (410.5 vs. 269.7 ng/ml, p = 0.03). Multivariate logistical regression model assessed high level of serum periostin, male gender, atopy, family history of asthma, and severity of the attack as significant risk factors for persistent compared to intermittent wheezing (r < sup > 2 < /sup > = 0.87, p = 0.04). Conclusions. Our results demonstrated that recurrent viral-induced wheezing is associated with decreased IFN-γ production and increased periostin response and their correlation with severity and persistence of symptoms were the main outcome measures.